Applying 3D cultures and high-throughput technologies to study host-pathogen interactions - De Martinis, Elaine Cristina Pereira; Alves, Virgínia Farias; Pereira, Marita Gimenez; Andrade, Leonardo Neves; Abichabki, Nathália; Abramova, Anna; Dannborg, Mirjam; Bengtsson-Palme, Johan (Frontiers in Immunology, 2025)
Recent advances in cell culturing and DNA sequencing have dramatically altered the field of human microbiome research. Three-dimensional (3D) cell culture is an important tool in cell biology, in cancer research, and for studying host-microbe interactions, as it mimics the in vivo characteristics of the host environment in an in vitro system, providing reliable and reproducible models. This work provides an overview of the main 3D culture techniques applied to study interactions between host cells and pathogenic microorganisms, how these systems can be integrated with high-throughput molecular methods, and how multi-species model systems may pave the way forward to pinpoint interactions among host, beneficial microbes and pathogens.